2004
DOI: 10.1038/sj.ejcn.1602051
|View full text |Cite
|
Sign up to set email alerts
|

Moderate alcohol consumption and levels of antioxidant vitamins and isoprostanes in postmenopausal women

Abstract: Background: Although alcohol intake has been positively associated with breast cancer risk in epidemiologic studies, the mechanisms mediating this association are speculative. Objective: The Postmenopausal Women's Alcohol Study was designed to explore the effects of moderate alcohol consumption on potential risk factors for breast cancer. In the present analysis, we evaluated the relationship of alcohol consumption with antioxidant nutrients and a biomarker of oxidative stress. Design: Participants (n ¼ 53) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 37 publications
2
21
0
Order By: Relevance
“…In accordance with this, elevated levels of isoprostanes have been detected in situations associated with increased free radical generation, in HIV-1-infected individuals, in postmenopausal women, and in chronic cigarette smokers (33,53). Similarly, increased production of arachidonic acid from different sources associated with various pathological conditions has been reported (47).…”
Section: Coculturing Of Infected T Cells With Neurons or Neurons Exposupporting
confidence: 52%
See 2 more Smart Citations
“…In accordance with this, elevated levels of isoprostanes have been detected in situations associated with increased free radical generation, in HIV-1-infected individuals, in postmenopausal women, and in chronic cigarette smokers (33,53). Similarly, increased production of arachidonic acid from different sources associated with various pathological conditions has been reported (47).…”
Section: Coculturing Of Infected T Cells With Neurons or Neurons Exposupporting
confidence: 52%
“…The detection of isoprostanes in vivo is used as a quantitative index for the existence of oxidative stress and also as a biomarker for certain types of diseases, such as cancer (33,79). In accordance with this, elevated levels of isoprostanes have been detected in situations associated with increased free radical generation, in HIV-1-infected individuals, in postmenopausal women, and in chronic cigarette smokers (33,53).…”
Section: Coculturing Of Infected T Cells With Neurons or Neurons Expomentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, recent studies have consistently shown that red wine and white wine also have beneficial effects in vivo on blood antioxidant activity (71,72,75,159). However, alcohol has also been found to exhibit a pro-oxidant effect (72,74,160). Some studies suggest that the antioxidant or pro-oxidant activities of alcoholic beverages may depend on factors, such as dose, ethanol content, polyphenol content, ethanol metabolism, and cell type (73,(161)(162)(163)(164)(165), but this is still unclear.…”
Section: Epidemiology Of Breast Cancer: Role Of Lipid Peroxidationmentioning
confidence: 99%
“…Several previous studies have applied urinary isoprostane as biomarkers of oxidative stress in general. The formation of isoprostane is related to personal factors (age) (Dohi et al, 2007), occupational exposure (welding fume) (Han et al, 2005), life style (vitamin C, vitamin E supplementation (Huang et al, 2002), smoking, (Dietrich et al, 2002;Dietrich et al, 2003), vegetable and fruit intake (Thompson et al, 2005), and alcohol consumption (Hartman et al, 2005), and occurrence of chronic diseases (asthma, atherosclerosis, ischemia-reperfusion, cardiovascular disease (Cracowski, 2004), systemic lupus erythematosus, inflammatory rheumatic disease, diabetes mellitus (Cracowski et al, 2002), and breast cancer (Rossner et al, 2006). Il'yasova et al (2004) indicated that ELISA measurements overestimates F2-Isoprostane levels than the GC/MS measurements.…”
Section: Discussionmentioning
confidence: 99%